Thermal Performance Analysis of a Linear Fresnel Solar Thermal Collector System - Okafor I. F.; Okeke I. D. (Current Approaches in Engineering Research and Technology Vol. 9, 2024)
Linear Fresnel solar collector is a line-focusing concentrator suitable for direct steam generation, industrial process heat applications, solar space cooling systems, and hot water generation for different uses. Experimental and numerical studies on the thermal performance of linear Fresnel solar collectors were reviewed. The advantages of a linear Fresnel solar collector over the parabolic trough solar collector were highlighted. The studies indicated that the thermal losses from the receiver cavity of a linear Fresnel solar collector are dominated by radiation followed by convection and conduction losses and these losses drastically reduced the thermal efficiency of the collector system. The studies also indicated that the thermal performance of the collector is influenced by the transmissivity of the glass pane, reflectivity, emissivity, and wall insulation of the receiver cavity. Thermal modeling of the collector system was based on steady-state uniform solar flux assumptions, rather than non-uniform solar flux boundary as indicated in the ray-tracing studies. Transient modeling for non-uniform solar flux boundary and heat flow in the receiver cavity is lacking in the literature. Studies are lacking on asymmetrical non-uniform solar flux distribution boundaries in terms of gravity. The studies also indicated that the thermal performance of a linear Fresnel solar collector still requires significant improvement by improving its thermal design models and heat transfer characteristics of its receiver system.